2014
DOI: 10.1088/0952-4746/34/4/775
|View full text |Cite
|
Sign up to set email alerts
|

32P measurement of urine samples and internal dose assessment for radiation workers in life science laboratories

Abstract: (32)P measurements of urine samples and internal dose assessments were conducted for workers in life science laboratories. A procedure for sample pre-treatment was established and validation was performed to exclude interference and to detect (32)P levels accurately. The detection conditions for Cherenkov radiation were evaluated and the accuracy of Cherenkov radiation measurements validated. The analytical and measurement procedures were applied to urine samples collected from 11 workers from life sciences la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Interviews of the workers revealed that the department primarily performed radioisotope (RI) injections, gamma camera imaging, RI distribution/administration, and PET-CT scans. The beta concentrations in urine samples ranged between 42.0-176.4 Bq l −1 , which were below the background levels of normal individuals (250 Bq l −1 ) [6]. WBC results showed that workers in charge of gamma cameras and pharmaceutical manufacturing had body burdens of approximately 6700 Bq, while those in charge of RI injections had approximately 1400 Bq.…”
Section: Internal Contamination Monitoring Of Workers In the Medical ...mentioning
confidence: 89%
See 1 more Smart Citation
“…Interviews of the workers revealed that the department primarily performed radioisotope (RI) injections, gamma camera imaging, RI distribution/administration, and PET-CT scans. The beta concentrations in urine samples ranged between 42.0-176.4 Bq l −1 , which were below the background levels of normal individuals (250 Bq l −1 ) [6]. WBC results showed that workers in charge of gamma cameras and pharmaceutical manufacturing had body burdens of approximately 6700 Bq, while those in charge of RI injections had approximately 1400 Bq.…”
Section: Internal Contamination Monitoring Of Workers In the Medical ...mentioning
confidence: 89%
“…Educational institution workers mainly consisted of those who worked in biochemistry departments and pharmacies. In a previous survey, internal contamination was reported in two workers from educational institutions, and their urine samples showed 15.2-24.6 Bq l −1 of P-32 [6]. Fluorescent substances are being increasingly used by educational institution workers to replace radioactive materials and provide protection against internal contamination.…”
Section: Workers At Educational and Research Institutesmentioning
confidence: 99%